Sistem Pakar Diagnosa Penyakit Autis Pada Anak-Anak Menggunakan Metode Fuzzy Logic - Iqbal, Iqbal; Husna, Asmaul (Jurnal Tika, 2023)
Autism is a disease caused by disorders of the brain. There are many types of child development disorders that parents are not aware of. One of the child development disorders is autism. The variables supporting the diagnosis of the disease are used in the formation of fuzzy sets. The fuzzy set will produce a definite decision. The purpose of this thesis research is to build an expert system that is capable of making disease diagnosis decisions in accordance with the knowledge of experts or doctors. Meanwhile, expert system development tools use the PHP and MySQL programming languages. The designed application has been tested involving diagnostic medical records from doctors or specialists in autism in children, the results of the decisions produced by the application are the same as the doctor's diagnoses listed in the medical record. In general, this web-based Expert System application can be used as a tool or companion in diagnosing autism in humans without having to directly consult a doctor face to face